Pengaruh Media Pembelajaran Terhadap Hasil Belajar Pendidikan Agama Islam di MTs Daarus Sa’adah Cipondoh Tangerang - Almaydza Pratama Abnisa; Zubairi Zubairi (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the effect of learning media on student learning outcomes in class VII MTs Daarus Sa'adah Cipondoh Tangerang subject of Islamic Religious Education. The hypothesis being tested is that there is a significant effect of learning media on the learning outcomes of class VII students of MTs Daarus Sa'adah Cipondoh Tangerang. This research was conducted using survey and quantitative descriptive methods. The research population was an affordable population, namely class VII students of MTs Daarus Sa'adah Cipondoh Tangerang, totaling 101 students. While the sample was taken by random sampling technique, namely 40 students, taken 39% of the reachable population. The data collected was analyzed using statistical techniques such as regression tests to identify the relationship between the use of instructional media and student learning outcomes. The research instrument for measuring learning media uses a questionnaire (questionnaire). Validity is calculated using the product moment correlation technique. Reliability is calculated by Alpha Cronbach formula. The test results show that 24 items are declared valid, and the reliability of r count = 0.9. The analysis requirements test is the normality test using the Liliefors test and the homogeneity test using the Fisher test. Inferential Analysis (Hypothesis Test) with simple regression and correlation analysis. The results of the study concluded that learning media had a significant effect on student learning outcomes in class VII SMP MTs Daarus Sa'adah Cipondoh Tangerang, with a correlation coefficient = 0.94 at a significance level of 0.05. From these results it is hoped that it will be useful for a teacher to improve the quality of his learning by using the latest and most interesting media so that he can deliver better learning outcomes and better achievement.